Non-contact tracking of shoulder bones using ultrasound and stereophotogrammetry - Sewify, Ahmed; Lavaill, Maxence; O’Rourke, Dermot; Antico, Maria; Pivonka, Peter; Fontanarosa, Davide; Martelli, Saulo (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeWe explored the integration of 3D ultrasound (US) imaging with motion capture technology for non-invasively tracking bones of the shoulder district during normal activity. Our study aimed to demonstrate ex-vivo the proposed 3D US method’s feasibility and accuracy of tracking shoulder bones in a controlled cadaveric shoulder positioned in various arm elevations (low, mid and high).MethodWe registered previously acquired full bone shapes to spatially small bony surface patches segmented from 3D US. The bone registration approach used was based on in silico analyses that investigated the effects of different — 1) registration algorithms (Iterative-Closest-Point–ICP, and Coherent Point Drift–CPD) and 2) initial estimate levels of the bone model pose relative to the targeted final bone pose—on the overall registration efficiency and accuracy in a controlled environment.ResultsCPD provided the highest accuracy in the simulation at the cost of 8x longer computation compared to ICP. The RMSE errors were <1 mm for the humerus and scapula at all elevations. Ex-vivo, the CPD registration errors were (Humerus = 2 mm and Scapula = 13.9 mm) (Humerus = 7.2 mm and Scapula = 16.8 mm) and (Humerus = 14.28 mm and Scapula = 27.5 mm), for low, medium and high elevations respectively.ConclusionIn summary, we demonstrated the feasibility and accuracy of tracking shoulder bones with 3D US in a simulation and a cadaveric experiment. We discovered that CPD may be a more suitable registration method for the task than ICP. We also discussed that 3D US with motion capture technology is very promising for dynamic bone tracking, but the US technology may not be ready for the task yet.